2019
DOI: 10.1371/journal.pone.0211080
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic efficacy of Aqui-S, Benzoak, and MS-222 on lumpfish (Cyclopterus lumpus) fries. Impact from temperature, salinity, and fasting

Abstract: Large numbers of lumpfish are produced for the Norwegian salmon industry and are used to combat sea lice infestations. Periodically high mortality of farmed lumpfish demonstrates the need to improve farming conditions and animal welfare. As part of such efforts, the present work tested the efficacy of three anaesthetic chemicals on lumpfish fries (average weight of 0.97 g). The anaesthetic impact from salinity (15 ppt–18 ppt), temperature (12°C versus 7 and 18°C), and fasting conditions (three days) was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As far as age is concerned, MS‐222 differences have been described between embryo‐larval stages and more developed stages such as juvenile and adults (Ehrlich et al, 2019) due to changes in metabolic rate and oxygen consumption during ontogeny (Rombough, 2011) that may affect the absorption of drugs and anaesthesia induction. In addition, these physiological and metabolic changes are dependent on water characteristics with temperature‐ (Jacobsen et al, 2019; Skar et al, 2017; Zahl et al, 2009), oxygen‐ (Carter et al, 2011; Topic Popovic et al, 2012) and pH‐dependent (Christiansen & Stoskopf, 2013) effects being reported for MS‐222. In a similar way, different studies have reported water characteristics dependent effects between and within different monoterpenes (Cavali et al, 2020; Gomes et al, 2011; He et al, 2020; Yousefi et al, 2019, 2022; Zapata‐Guerra et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As far as age is concerned, MS‐222 differences have been described between embryo‐larval stages and more developed stages such as juvenile and adults (Ehrlich et al, 2019) due to changes in metabolic rate and oxygen consumption during ontogeny (Rombough, 2011) that may affect the absorption of drugs and anaesthesia induction. In addition, these physiological and metabolic changes are dependent on water characteristics with temperature‐ (Jacobsen et al, 2019; Skar et al, 2017; Zahl et al, 2009), oxygen‐ (Carter et al, 2011; Topic Popovic et al, 2012) and pH‐dependent (Christiansen & Stoskopf, 2013) effects being reported for MS‐222. In a similar way, different studies have reported water characteristics dependent effects between and within different monoterpenes (Cavali et al, 2020; Gomes et al, 2011; He et al, 2020; Yousefi et al, 2019, 2022; Zapata‐Guerra et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of anesthetic agents in aquatic species is affected by biotic and abiotic factors, such as size, age, sex, salinity, pH, oxygen level, and water temperature [ 24 , 27 , 28 , 29 , 30 ]. Among these factors, temperature is arguably the most critical one [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study with marketable-size Nile tilapia (400–600 g), the determined optimal doses of MS-222 (300 µg/mL) and eugenol (90 µg/mL) [ 22 ] were higher than the doses for tilapia fries (3 g), which were 105 and 20 µg/mL, respectively [ 35 ]. Likewise, the effective doses of MS-222 for anesthetizing large-size (200–1300 g) and small-size lumpfish (10–20 g) were 200 and 100 µg/mL, respectively [ 21 ], while the appropriate dose for lumpfish fries (1 g) was only 60 µg/mL [ 29 ]. Nevertheless, it is worth mentioning that the relationship between a fish’s body weight and anesthetic action is not always straightforward [ 8 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…51 In terms of husbandry and logistics, participants highlighted problems surrounding the optimal timing and frequency of grading, the correct use of shelters 73 and tank enrichment, the development of a breeding programme 13 and the practical difficulties of separating lumpfish from salmon prior to cage treatment. Other, less pervasive challenges related to optimal light levels which are poorly known in lumpfish, 27,74 the choice and use of anaesthetics, 75 poor water quality and permissible bacteria loads, 76,77 lack of specific facilities for the rearing of the species, and the logistic constraints caused by working at remote sites. The challenge of balancing the welfare needs of lumpfish with efficiency in salmon production and a tendency to prioritise the needs of Atlantic salmon over those of lumpfish 44 were also flagged as particular issues.…”
Section: Challenges (N = 40) Weightmentioning
confidence: 99%